Ibrutinib in c-MYC and HER2 Amplified Oesophagogastric Carcinoma: Results of the Proof-of-Concept iMYC Study - Fiona Turkes (Current Oncology, 2022)
Oesophagogastric (OG) cancer is a highly lethal disease requiring novel treatment options. c-MYC and/or HER-2 amplified oesophageal cancer models have demonstrated sensitivity to BTK inhibition with ibrutinib. We evaluated the safety and efficacy of ibrutinib in patients with c-MYC and/or HER2 amplified pre-treated advanced OG cancer. c-MYC and HER2 amplification status were determined by FISH. The primary endpoint was overall response rate (ORR). Secondary endpoints were disease control rate (DC) at 8 weeks, safety, progression-free survival (PFS) and overall survival (OS). Eleven patients were enrolled. Eight patients had c-MYC amplified tumours, six were HER2 amplified and three were c-MYC and HER2 co-amplified. Grade ≥ 3 adverse events were fever, neutropenia, and vomiting. Grade ≥ 3 gastrointestinal haemorrhage occurred in three patients and was fatal in two cases. Among seven evaluable patients, three patients (43%) achieved a best response of SD at 8 weeks. No PR or CR was observed. Disease control was achieved for 32 weeks in one patient with a dual c-MYC and HER2 highly co-amplified tumour. The median PFS and OS were 1.5 (95% CI: 0.8–5.1) and 5.1 (95% CI: 0.8–14.5) months, respectively. Ibrutinib had limited clinical efficacy in patients with c-MYC and/or HER2 amplified OG cancer. Unexpected gastrointestinal bleeding was observed in 3 out of 8 treated patients which was considered a new safety finding for ibrutinib in this population.